Effects of Qihuang Needling on Motor Function for Patients With Parkinson's Disease: Study Protocol for a Multicenter, Randomized Controlled Trial - Yang, Lian-Sheng; Li, Yang-Mei; Zhou, Dan-Feng; Zhao, Bai-Ming; Zheng, Shu-Zhen; Chen, Zhen-Hu; Zhang, Kun; Lu, Li-Ming (Frontiers in Neurology, 2022)
Background Although significant progress has been made in the pharmacologic management of Parkinson's Disease (PD), effective management of movement disorders is still a hurdle for therapeutics targeting PD. Acupuncture is one therapeutic option that could potentially improve the motor function of PD and is widely used as adjuvant therapy. Among the various acupuncture approaches, Qihuang Needling (QHN) therapy has been found to improve motor-function control for patients with PD. However, evidence regarding its efficacy remains scarce. Therefore, to address this need, this study will determine the effects of QHN therapy on motor function in patients with PD and compare it to placebo effects. Methods This trial is a multicenter, prospective randomized controlled clinical trial. We randomly allocated 144 participants to two groups of 72 patients. Patients in the treatment group were treated with QHN therapy. The control group had undergone insertion of acupuncture needles at sham acupoints not corresponded to acupuncture points. Participants in the verum treatment group and sham-acupuncture control group received 9 sessions over 6 weeks followed by 8 weeks of follow-up. The primary outcome was the change of motor function from baseline to weeks 6 and 14 measured by the PD Rating Scale-Part III Motor Examination (UPDRS-III). Secondary outcome measures included the change of PD daily quality of life-39 (PDQ-39) and Non-Motor Symptoms Scale for PD (NMSS) from baseline to weeks 6 and 14. Discussion The results of this trial will generate data to improve our general understanding of the efficacy of QHN therapy on motor function in patients with PD and thoroughly compare these responses to the placebo effect. Trial Registration The trial was registered at the Chinese Clinical Trials Registry (ChiCTR- 2000030871) on 16 March 2020.